O ENADE (Exame Nacional de Desempenho de Estudantes) sob a ótica de alunos de administração. - Valluis, Marcel André (2014)
This dissertation analyzes the Enade (National Examination Performance of Students), one of the external assessments within the Sinaes (National Evaluation System of Higher Education), established by Law 10.861, of April 14, 2004, with the purpose of assessing HEI (Higher Education Institutions), the courses and performance of college students. The objective of this research is to analyze the impact of this examination on the graduating students of Business. The study is based on official documents, references on higher education in Brazil, its quality and on the current assessment policy. The research comes from the experience of the author, who is a professor and coordinator of the Business course and investigates a group of students from a HEI. It adopts a qualitative approach, conducted like as a case study, drawing on consultation with the subject using a questionnaire with open and closed questions. Responses to the questionnaire indicate that subjects perceive the Enade as an evaluating instrument of the training received in the course, they would do it spontaneously and that, from their perspective it contributes to improving the quality of higher education in Brazil. The results obtained from the research can be added to the other researches dealing with national examinations and assessment in higher education, as well as indicate to managers and teachers of HEI, alternatives to better incorporate this type of external evaluation to their daily routine without compromising their autonomy, and better understand the challenges faced by the course that meets working students, aged between 21 and 45, who come from public schools.